POLITICAL COMMUNICATION IN DEVELOPMENT: NARRATIVE CONTESTATION AND THE LEGITIMACY OF PUBLIC POLICY IN THE TUBAN OIL REFINERY PROJECT - Martinus Itte; Amirul Mustofah; Aris Sunarya (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze political communication of development in the contestation of narratives and public policy legitimacy within the Tuban Oil Refinery Project. The project, developed by PT Pertamina (Persero), is positioned as part of Indonesia’s strategic national agenda to strengthen energy security and economic growth. This research employs a qualitative approach with a case study design, utilizing in-depth interviews, observation, and document and media analysis. The findings reveal that the government constructs development framing based on rational-legal legitimacy and performance legitimacy through predominantly top-down and informative communication patterns. However, at the local level, particularly in Tuban, narrative contestation emerges between official state discourse and community counter-narratives concerning land acquisition and environmental impacts. Policy legitimacy is found to be dynamic and continuously negotiated within the public sphere, including social media platforms. The study concludes that the success of strategic national projects depends not only on administrative and regulatory effectiveness but also on dialogical and participatory political communication.